In vitro evaluation of microleakage of class II packable composite resin restorations using flowable composite and resin modified glass ionomers as intermediate layers - Majety, Kishore Kumar (Medknow Publications & Media Pvt Ltd, 2011)
AIM AND OBJECTIVES: To evaluate the cervical marginal microleakage of class II packable composite resin restorations using flowable composite and resin modified glass ionomer as intermediate layers and whether the difference in the thickness of these intermediate layers would influence the microleakage. MATERIALS AND METHODS: Standardized class II box only cavities (4 mm bucco lingual width 2 mm mesio distal depth with the gingival margin 1 mm above the cemento-enamel junction (CEJ) were restored as follows: Group A Restoration with packable composite alone, Group B, Subgroup 1, 1 mm flowable composite liner + packable composite, Sub Group 2, 2 mm flowable composite liner + packable composite, Group C, Subgroup 1, 1 mm resin modified glass ionomer cement (RMGIC) liner + packable composite, Sub Group 2, 2 mm RMGIC liner + packable composite, The specimens were thermocycled, stained with methylene blue, sectioned to evaluate the dye penetration. Data were analyzed using Kruskall Wallis Test and Mann Whitney U test. RESULTS: There was no statistically significant difference between the groups. The difference in the thickness of the intermediate layers did not influence the microleakage. CONCLUSIONS: Use of 1 mm of flowable composite intermediate layer improved the sealing ability of packable composites than the differential thickness of resin modified glass ionomer.